ChemInform Abstract: Asymmetric Transfer Hydrogenation of α‐Amino β‐Keto Ester Hydrochlorides Through Dynamic Kinetic Resolution. Issue 46 (November 2015) - Echeverria, Pierre‐Georges; Cornil, Johan; Ferard, Charlene; Guerinot, Amandine; Cossy, Janine; Phansavath, Phannarath; Ratovelomanana‐Vidal, Virginie
Abstract The asymmetric transfer hydrogenation of α‐amino β‐keto ester hydrochlorides is reported for the first time using a ruthenium catalyst in combination with ammonium formate as the hydrogen source.